Financial economics Quantitative and qualitative assessments - Vrinda Arora (New Delhi Random Publications, 2021)
Introduction to financial economics; theories of financial economics; financial analysis; qualitative model; traditional approach to portfolio; financing decisions; corporate finance; monetary theory in economy; economics of information products; capital market investment.
Keywords: Financial economics